AKIBAT HUKUM PEMBATALAN HIBAH TERHADAP BANGUNAN YANG DIDIRIKAN DI ATAS TANAH HIBAH (STUDI KASUS PUTUSAN MAHKAMAH SYAR’IAH ACEH NO 93/PDT.G/2015/MS-ACEH) - MAISYARAH - - (PREMISE LAW JURNAL, 2017)
ABSTRACT Hibah (grant) is a direct handover unconditionally, without self-interest. In a legal act, it is a transfer of right of a person’s property to other people free of charge, without expecting anything in return. It cannot be withdrawn except it is from parents to their children as it is stipulated in Article 212 of KHI (Compilation of the Islamic laws. The research used normative juridical research and descriptive analytic method. The primary and secondary data were gathered by conducting library research and field research and analyzed qualitatively, and the conclusion was drawn deductively. The result of the research shows that a hibah actually cannot be revoked except it has been given by parents to their children as it is embodied in the Hadist and in the KHI. The building which has been built on the hibah land will automatically be owned by the person who built it, and the land which hibah is revoked will be owned by the giver of hibah so that the building built on it becomes illegal since it has no legal basis. Judge’s consideration in the Ruling is in accordance with the prevailing regulation since he uses Hadist and the KHI in his consideration. Keywords: Hibah, Revocation of Hibah, Building